The reliability of a subtype-determining questionnaire in efficient benign paroxysmal positional vertigo diagnosis in geriatrics - Yichen Wan; Yingxuan Li; Jianjun Sun (Frontiers in Aging Neuroscience, 2023)
IntroductionBenign paroxysmal positional vertigo (BPPV), the most common cause of dizziness, especially for older adults, exposes patients to the lethal risk of falling. However, the diagnosis of BPPV in this population can be more elusive as they present few characteristic symptoms. Therefore, we explored the application of a subtype-determining questionnaire in BPPV diagnosis among the geriatric population.MethodsPatients were assigned to the aware and unaware groups. In the aware group, the technician would directly test the suspected canal indicated by the questionnaire, whereas, in the unaware group, the technician performed the regular positional test. The diagnostic parameters of the questionnaire were examined.ResultsThe accuracy, sensitivity, and specificity of questions 1–3 for diagnosing BPPV were 75.8, 77.6, and 74.7%, respectively. Question 4 demonstrated an accuracy of 75.6% in ascertaining the BPPV subtype, question 5 showed an accuracy of 75.6% in determining the affected side, and question 6 yielded an accuracy of 87.5% in distinguishing canalithiasis or cupulolithiasis. Examination time was shorter in the aware group than that in the unaware group (P < 0.05). No difference was found between the two groups for treatment time (P = 0.153).ConclusionThis subtype-determining questionnaire is practical in daily use and capable of providing instructive information for an efficient diagnosis in geriatric patients with BPPV.